Peran Media Sosial dalam Keterlibatan Politik Generasi Z - Putri, Selviana; Prihardini Wibawa, Dian (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to examine the relationship between the quality of social media information, social media political marketing activities, trust and political involvement of the generation z. Empirical analysis was carried out using a sample of 156 generation z. This research uses an online survey for data collection. After passing the reliability and validity tests, the data was analyzed using a partial least squares structural equation model. The research results state that the quality of social media information has a direct positive and significant influence on trust. The quality of social media information also has a significant indirect impact on trust. However, there is no significant relationship between information quality and political involvement. Political engagement is significantly influenced by social media marketing initiatives that increase trust, both directly and indirectly. Finally, trust has a strong and positive impact on political participation.